Conflict in Private Land: The Role of “Yellow Journalism” in the Turmoil of Batu Ceper, Tangerang 1934 - Muhamad Mulki Mulyadi Noor; Susanto Zuhdi (IHiS (Indonesian Historical Studies), 2020)
This article discusses the conflict and social unrest in the Batu Ceper private lands. The events in Batu Ceper was an example of anti-extortion movement erupted due to the Cuke and Kompenian problems against the background of the socio-economic issuessince the late 19th century. This study identifies “yellow journalism” concept which succeeded in uplifting the Batu Ceper event with a bombastic and sensational headline in the form of an exciting debate between the newspapers of the landlord’s defender (the white press) and the peasant advocates (press Indonesier). The victory of the white press in the court did not mean the end of potential chaos, because the anxiety which became the factor of chaos never faded away due to a mere court ruling. This article reflects the field of social history, in which the study uses mass media as its primary focus. It shows the characteristic of disruption in a historical perspective.